Revisiting the Cytotoxicity of Cationic Polyelectrolytes as a Principal Component in Layer-by-Layer Assembly Fabrication - Ekaterina Naumenko; Farida Akhatova; Elvira Rozhina; Rawil Fakhrullin (MDPI AG, 2021)
Polycations are an essential part of layer-by-layer (LbL)-assembled drug delivery systems, especially for gene delivery. In addition, they are used for other related applications, such as cell surface engineering. As a result, an assessment of the cytotoxicity of polycations and elucidation of the mechanisms of polycation toxicity is of paramount importance. In this study, we examined in detail the effects of a variety of water-soluble, positively charged synthetic polyelectrolytes on in vitro cytotoxicity, cell and nucleus morphology, and monolayer expansion changes. We have ranked the most popular cationic polyelectrolytes from the safest to the most toxic in relation to cell cultures. 3D cellular cluster formation was disturbed by addition of polyelectrolytes in most cases in a dose-dependent manner. Atomic force microscopy allowed us to visualize in detail the structures of the polyelectrolyte-DNA complexes formed due to electrostatic interactions. Our results indicate a relationship between the structure of the polyelectrolytes and their toxicity, which is necessary for optimization of drug and gene delivery systems.